Whole and peak physical characteristics of elite youth female soccer match-play. Issue 12 (18th June 2021) - Harkness-Armstrong, Alice; Till, Kevin; Datson, Naomi; Emmonds, Stacey
ABSTRACT: This study quantified whole and peak physical characteristics of Under (U)14 and U16 elite youth female soccer, and compared by position and age-group. Data was collected using 10 Hz GPS units from 431 match observations, during 50 matches involving 201 players (U14 n = 93; U16 n = 108) representing Regional Talent Centres in The Football Association's Girl's England Talent Pathway League. Whole match data were reported as absolute and relative; total (TD), high-speed running (HSR; ≥3.46 m·s −1 ), very high-speed running (VHSR; ≥5.29 m·s −1 ), and sprinting (SPR; ≥6.26 m·s −1 ) distance, and maximum velocity. Moving average analysis determined peak data (1–10 minute durations). Linear mixed models established position-specific differences. U16s covered greater; absolute distance at all speeds (small-moderate ESs; p < 0.001); relative VHSR and SPR m·min −1 (small-moderate ESs; p < 0.001); peak TD and HSR m·min −1 (small ESs) across several peak-durations, and VHSR m·min −1 (small ESs; p < 0.001) across all peak-durations compared to U14s. Position-specific differences were observed across all positions between and within both age-groups, identifying whole and peak physical characteristics are age- and position-dependent within elite youth female soccer match-play. Findings may facilitate informed coaching practices and training programme design, talent identification and development processes.